Neuropsychopharmacological Aspects of Antibiotic Action - Yu. A. Sergeev; E. V. Beyer (Антибиотики и Химиотерапия, 2025)
The review summarizes current data from experimental and clinical studies on the properties of antibiotics from the point of view of neuropsychopharmacology. Against the background of pronounced antibiotic resistance, the side effects of such drugs are of potential interest. Therefore, the possibility of the latter influencing mental functions, cognitive status, nociceptive system, as well as their involvement in the development of sleep disorders, are of particular interest.